A BEHAVIORAL MODEL FOR MEASURING UNIVERSITY CLIMATE ENTREPRENEURSHIP SEBAGAI SALAH SATU SOLUSI KESEJAHTERAAN KELUARGA DI SURABAYA - Christina Esti Susanti (Research Center and Case Clearing House PPM School of Management, 2014)
This study uses a model of behavior that involves the integration of individuals, organizations, and institutions as determinant factors and their effects on academic entrepreneurial behavior. In a comprehensive model of behavior puts academic entrepreneurial intention as intervening varible that affect academic entrepreneurial behavior. Academic entrepreneurial intentions are directly affected by the perceived desirability, perceived feasibility, and innovation values fit. And these variables indirectly affect academic entrepreneurial behavior. This behavioral model using Structural Equation Modeling (SEM) as a tool to test the statistical test that the institutional environment which will positively affect mempengarruhi individual entrepreneurial intentions among members of the university community as a solution to the welfare of the family. The results of this study prove that all proposed hypothesis is accepted.